Hard choices security, democracy, and regionalism in Southeast Asia - Emmerson, Donald K. (Walter H. Shorenstein Asia-Pacific Research Center, 2008)
Security has long trumped democracy as a priority for the Association of Southeast Asian Nations (ASEAN). But the brutal dictatorship in Burma/Myanmar, political pluralism in Indonesia, and the global growth of democratic norms have led some Southeast Asians to question ASEAN's habit of turning a blind eye to domestic abuses by member states. The concept of regional security, meanwhile, is being reoriented from military threats toward new dangers to health and the environment and from state security toward human security. Will promoting democracy cause local autocrats to hunker down and split ASEAN into hostile camps? Will ignoring demands for democracy allow domestic pressures to rise to dangerous levels? Should Burma/Myanmar be expelled or engaged? How should ASEAN respond to nontraditional threats to security in which member states are themselves implicated? In Hard Choices, experts grapple with these and other key and controversial questions for Southeast Asia today and tomorrow.505